Microwave-assisted extraction of sulfated polysaccharides(fucoidan)from brown seaweed - Rodríguez-Jasso, Rosa María (2011)
Sulfated polysaccharides (fucoidan) were recovered from brown seaweed Fucus vesiculosus by microwave-assisted extraction (MAE). Different conditions of pressure (30 to 120 psi), extraction time (1 to 31 min), and alga/water ratio (1/25 to 5/25 g ml-1) were evaluated during this process aiming to establish a condition to maximize the extraction results. The alga degradation (%), total sugar yield (%), and SO3 content (%) were also determined to each experimental condition. All the studied variables presented significant (p<0.05) influence on fucoidan yield. MAE at 120 psi, 1 min, using 1 g alga/25 ml water was the best condition for the fucoidan recovery. L-fucose was the main constituent of this polysaccharide, which also contained xylose and galactose. MAE under optimum reaction conditions was an effective method to recover fucoidan from Fucus vesiculosus. This method required short extraction times, and non corrosive solvents, resulting in reduced costs and being an environmentally friend technique.